Mechanical and physical properties of chitosan-compatibilized montmorillonite-filled tapioca starch nanocomposite films - Abdul Ghani, Siti Waqina (SAGE Publications Ltd, 2016)
Chitosan-compatibilized montmorillonite-filled plasticized tapioca starch (thermoplastic starch) nanocomposite films were produced using a solution casting method. Chitosan used was prepared and produced from the local shrimp shells. X-ray diffraction analysis showed that the interlayer spacing of the chitosan-compatibilized montmorillonite/thermoplastic starch films was slightly increased which indicated that the chitosan was too large to intercalate into the clay galleries. However, a scanning electron microscopy analysis showed that the compatibilized films produced a more homogeneous distribution of montmorillonite nanoclay particulate compared to the uncompatibilized films. The water vapor transmission rate, water absorption, and light absorbance thermoplastic starch films decreased with increasing chitosan and decreasing montmorillonite content. The increased chitosan content from 5 to 9 wt% with decreased montmorillonite content from 7 to 3 wt% improved flexibility about 53%, water resistance 66%, water vapor transmission rate resistance 9%, and thermoplastic starch film light transmission with a moderate decrease, tensile strength about 12% and tensile modulus about 99%. Generally, the chitosan successfully acted as a compatibilizing agent between montmorillonite and starch by improving the properties, particularly on film flexibility, which is utilized for food packaging.